2016
DOI: 10.1007/s10067-016-3469-5
|View full text |Cite
|
Sign up to set email alerts
|

Generation and differentiation of induced pluripotent stem cells reveal ankylosing spondylitis risk gene expression in bone progenitors

Abstract: Axial spondyloarthritis (axSpA), which encompasses ankylosing spondylitis, is a complex genetic disease. Aberrant bone formation is a key feature of pathogenesis that can lead to ankylosis of the spine. Our objective is to determine, whether genes whose variants confer susceptibility to AS are expressed in bone progenitors like mesenchymal stem cells (MSCs). Since MSCs from bone marrow is difficult to obtain, we first examined, whether MSCs can be derived from induced pluripotent stem cells (iPSCs). Dermal fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Recently, our research, as well as that of other researchers, demonstrated that MSCs from AS patients (AS-MSCs) outperformed MSCs from healthy donors (HD-MSCs) in osteogenic differentiation in two-dimensional (2D) culture, which could be an important mechanism of pathological osteogenesis in AS 11,12 . However, whether AS-MSCs exhibit an enhanced osteogenic differentiation ability in vivo is still unclear.…”
Section: Introductionmentioning
confidence: 62%
“…Recently, our research, as well as that of other researchers, demonstrated that MSCs from AS patients (AS-MSCs) outperformed MSCs from healthy donors (HD-MSCs) in osteogenic differentiation in two-dimensional (2D) culture, which could be an important mechanism of pathological osteogenesis in AS 11,12 . However, whether AS-MSCs exhibit an enhanced osteogenic differentiation ability in vivo is still unclear.…”
Section: Introductionmentioning
confidence: 62%
“…Beyond direct iMSC-mediated effects, iMSCs have been demonstrated to have therapeutic paracrine effects, thus resulting in an attenuation of cardiomyopathy [ 12 ] and rejuvenation in aging [ 13 ]. In another application, disease-specific iMSCs have provided unparalleled opportunities as human cell-based disease models for pathological research, drug screening, and toxicity testing to discover novel therapeutic strategies for treating a variety of mesenchymal diseases, such as osteogenesis imperfecta [ 14 ], Hutchinson–Gilford progeria syndrome [ 15 ], axial spondyloarthritis [ 16 ], and fibrous dysplasia [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the whole blood components including neutrophils, lymphocytes, monocytes, and platelets were correlated with systemic inflammation [8][9][10]. Neutrophil to lymphocyte ratio (NLR), monocyte to lymphocyte ratio (MLR), and platelet to lymphocyte ratio (PLR) have been identified as new inflammatory markers and reported to be higher in axSpA patients and related to disease activity [11][12][13].…”
Section: Introductionmentioning
confidence: 99%